The Effect of Using the Media Matching Box in Improving the Ability of Number Recognition in Students - Fitriani, Diana; Mulia, Dedi; Abadi, Reza Febri (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2021)
This research was motivated by the problems that the researchers found in SKh Idaman Hati Tangerang City, namely in children with intellectual disabilities in class V in learning the introduction of numbers 1-5. This study aims to determine whether the use of matching box learning media has a significant effect in increasing the ability to recognize numbers at the stage of mentioning numbers 1-5 children with intellectual disabilities. The type of research used is experimental research with Single Subject Research. Data collection techniques used, namely observation, documentation, and instruments. Subjects involved in this study amounted to 1 child. The results showed that the ability to mention numbers 1-5 children with intellectual disabilities got an average percentage or mean level from the baseline-1 phase (A1), intervention (B), and baseline-2 phase (A2), namely 47%, 97.75% , and 87%. The data shows that children with intellectual disabilities experienced an increase in the percentage after receiving intervention through media matching boxes, so it can be concluded that the use of media matching boxes has an effect on increasing the ability to recognize numbers 1-5 in children with intellectual disabilities in class V at SKh Idaman Hati, Tangerang City